Resveratrol adsorption on carbon nanotubes: a first principles study - Schwarz, Stefanie Camile; Rossato, Jussane; Santos, Cláudia Lange dos; Zanella, Ivana; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
In this paper, the structural and electronic properties of carbon nanotubes in pristine and carboxylated form, interacting with resveratrol molecules, are studied through first principles calculations based on the Density Functional Theory. The results demonstrate that resveratrol molecules interact with carbon nanotubes with binding energies lower than 0.5 eV. There were no significant differences observed in the structural or in the electronic properties of the final systems. The interaction occurs via physical adsorption, which is a valuable property for carbon nanotube and for the purpose of its use as drug delivery systems.